WATER QUALITY MAPPING ON ESTUARY, BASED ON TOTAL SUSPENDED MATTER (TSM) APPROACH AT MUARA BOJONG SALAWE, PANGANDARAN, JAWA BARAT - Rizky Ramadhan, M
Muara Bojong Salawe (MBS) is one of the estuaries that is disturbed by sedimentation. This is because MBS is a confluence of three tributaries, namely Cijalu, Cijulang, and Cikiray rivers. The sedimentation problem at MBS becomes a threat because it can disrupt the balance of aquatic ecosystems, such as the decay, the soil of several aquatic ecosystems, and other environmental damage. With this problem, a necessary assessment of the water quality of estuaries against sedimentation, as an effort to monitor the condition of estuaries and minimize the negative impact of sedimentation. One of the approaches in assessing the quality of estuaries is by mapping the spread of total suspended matter (TSM), which is then assessed based on TSM quality standards on seawater. The TSM mapping is approached with regression modeling by calculating the correlation of the value of reflectance of the SPOT 6 image data with the concentration data of TSM observation results. Data processing is done using ArcMap software 10.7.1, ENVI 5.1, Microsoft Excel 365, and Global Mapper 2020. This research aims to map the quality of water based on the concentration of TSM in the MBS based on TSM quality standards on seawater. The results of this study are expected to provide an overview of the concentration of TSM so that it can be a reference in the rehabilitation of the region. The research location is in Muara Bojong Salawe, Pangandaran, West Java, with an area of study of about 194.7 hectares. The results of the research were obtained by five models with the best coefficient of determination (R2). Of the five models, the 3rd order polynomial regression equation model was chosen as the best model in estimating the distribution of TSM concentrations (R2= 0.53), which is define by the equation Y (TSM) mg/L = 108x3– 2 (107) x2+ 2 (106) x – 32112, with the Root Mean Square Error (RMSE) = 34.8 mg/L, as well as the accuracy value of 79%. The TSM mapping results showed that most of the areas did not comply with TSM quality standards on seawater (88.4% had a TSM content > 80 mg/L). The TSM distribution pattern tends to be concentrated on the confluence of the tributaries, the southern bay of estuary, and the estuary door leading to the sea. In the area, there is a high concentration of TSM that is between 100-250 mg/L.